The role of mast cells in allergic rhinitis - Jin Zhang; Xiaofei Xie; Ruixia Ma; Peng Liu (PeerJ, 2025)
Introduction In recent decades, mast cells and their mediators have been increasingly recognized as central players in the pathogenesis of allergic rhinitis (AR), a complex chronic nasal disease characterized by pathological changes influenced by genetic factors, various immune cells, and environmental exposures. Mast cells are pivotal in allergic reactions, orchestrating inflammation and airway contraction through the secretion of diverse mediators. Prominent among these mediators are histamine and bioactive lipids, whose physiological effects are prominently observed during the acute phase of allergic reactions. The accumulation of mast cells in specific areas of allergic rhinitis may correlate with the disease’s phenotype, progression, and severity. In vivo experiments in mice have demonstrated that mast cells develop from mast cell progenitor cells, which are induced by inflammatory stimuli and subsequently migrate to the airway. Human mast cell progenitor cells have been identified in the bloodstream, with a high proportion potentially reflecting the persistent pathological changes associated with allergic rhinitis. The primary activation of mast cells in allergic rhinitis occurs via the cross-linking of IgE high-affinity receptors (Fcɛ RI) mediated by IgE in conjunction with allergens. However, mast cells can also be activated by a variety of other stimuli, including toll-like receptors and MAS-related G protein-coupled receptor X2. Rationale for this review Despite the substantial progress in understanding the role of mast cells in allergic rhinitis, several critical gaps remain in our knowledge. The complex interplay between mast cells, their mediators, and the immune system in the context of AR is still not fully elucidated. Moreover, the specific mechanisms underlying the recruitment and activation of mast cell progenitor cells in the nasal mucosa remain poorly understood. Addressing these gaps is essential for developing more effective therapeutic strategies for allergic rhinitis. This review aims to provide a comprehensive and up-to-date synthesis of the current literature on the role and development of mast cells and their progenitor cells in allergic rhinitis, including the activation pathways implicated in the pathogenesis. Target audience This review is intended for a broad audience, including researchers in the fields of immunology, allergy, and respiratory medicine, as well as clinicians who manage patients with allergic rhinitis. By summarizing the latest findings and highlighting the unresolved questions, this review aims to serve as a valuable reference for future research directions in mast cells and allergic rhinitis, ultimately contributing to improved patient care and outcomes.